STUDY OF CONTEMPORARY ARCHITECTURE ISSUES ON THE HIDDEN GEMS BAR TAMBLONG BAR CONCEPT IN A RESTAURANT THROUGH THE ADAPTIVE REUSE CONCEPT - Kusumah, Indra Yudhapratama; Permana, Asep Yudi; Barliana, M Syaom; Permana Sari, Diah Cahyani (Journal of Development and Integrated Engineering, 2023)
This article discusses how urbanity, the originality of a city is an attraction for tourists to visit a tourist destination. One of the studies that is being discussed is the bar concept in Tamblong restaurants and bars, called Hidden Gems Bar Tamblong which has a potential for study as a form of contemporary architectural development issues and also of course another impact function is as a business that will have a positive impact on helping the economic development of the local community, also has the potential to attract tourists to visit. The research method used is a qualitative descriptive research method.